Intertextuality, intersubjectivity, and narrative identity - Gaál-Szabó, Péter (Cambridge Scholars Publishing, 2017)
"Intertextuality, Intersubjectivity, and Narrative Identity presents recent findings and opens new vistas for research by mapping the potential interconnections of intertextuality and intersubjectivity across a range of fields. Multidisciplinary in its focus, it incorporates various research foci and topoi across time and space. It is largely orchestrated around issues of identity in the fields of narration, gender, space, and trauma in British, Irish, American, South African, and Hungarian contexts. The contributions here centre on narrative identity, mediality, and spatiotemporality; modernism and revivalism; cultural memory, counter-histories, and place; female Künstlerdramas and war testimonies; and parasitical intersubjectivity, trauma, and multiple captivities in slave narratives. The volume brings together the seasoned insight of established researchers and the vivacious freshness of young scholars, providing an engaging read. Ultimately, it will prove to be relevant to researchers, teachers, and the general public given its unique approaches and the diversity of the topics explored"--Provided by publisher.